2014
DOI: 10.1007/s13272-014-0142-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PEMFC operation in ambient- and low-pressure environment considering the fuel cell humidification

Abstract: This paper summarizes experimental results of an air fed polymer electrolyte membrane fuel cell system HyPM XR 12 (Hydrogenics Corp.) considering fuel cell temperature, stoichiometry and load requirement variations at ambient and low pressure operation. The experimental work realized at a low pressure test facility designed and assembled by the German Aerospace Center, Institute of Engineering Thermodynamics is based on an experimental design. The experimental results confirm reduced fields of fuel cell operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Contrarily the low stoichiometry of 1.6 yielded better cathode exhaust gas quality with only 10% oxygen content [7]. High altitude/low pressure effects on fuel cells were studied under simulated conditions or within a system of small manned aircraft [26,30,40]. Relationship between pressure and altitude is defined as approximately 200, 2 000, 3 000 and 12 000 m above sea level and are equivalent to 1 to 0.9, 0.75, 0.7 and 0.2 bar respectively [7,11].…”
Section: Pemfc Stack Testing Under Aeronautic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily the low stoichiometry of 1.6 yielded better cathode exhaust gas quality with only 10% oxygen content [7]. High altitude/low pressure effects on fuel cells were studied under simulated conditions or within a system of small manned aircraft [26,30,40]. Relationship between pressure and altitude is defined as approximately 200, 2 000, 3 000 and 12 000 m above sea level and are equivalent to 1 to 0.9, 0.75, 0.7 and 0.2 bar respectively [7,11].…”
Section: Pemfc Stack Testing Under Aeronautic Conditionsmentioning
confidence: 99%
“…Relationship between pressure and altitude is defined as approximately 200, 2 000, 3 000 and 12 000 m above sea level and are equivalent to 1 to 0.9, 0.75, 0.7 and 0.2 bar respectively [7,11]. Altitude tests showed notable performance loss at 0.7 bar/2200 m altitude [20,26,30]. Further testing showed that the loss can be minimized by increasing air stoichiometry to 2.5 for altitudes higher than 2 000 m [30].…”
Section: Pemfc Stack Testing Under Aeronautic Conditionsmentioning
confidence: 99%
“…Yet, previous studies have demonstrated that the ambient conditions profoundly affect the PEMFC performance, 40,[75][76][77][78][79] indicating that it would be meaningful to incorporate ambient variations in the fault diagnosis model. Yet, previous studies have demonstrated that the ambient conditions profoundly affect the PEMFC performance, 40,[75][76][77][78][79] indicating that it would be meaningful to incorporate ambient variations in the fault diagnosis model.…”
Section: Introductionmentioning
confidence: 99%
“…None of the reported fault diagnosis techniques (among all mentioned techniques) directly incorporate the effect of ambient changes on the PEMFC. Yet, previous studies have demonstrated that the ambient conditions profoundly affect the PEMFC performance, 40,[75][76][77][78][79] indicating that it would be meaningful to incorporate ambient variations in the fault diagnosis model. This paper reports our attempt to combine two recent PEMFC models,, 5,52 to simultaneously model the voltage and temperature of the PEMFC.…”
mentioning
confidence: 99%
“…C. Werner found that the oxygen partial pressure and fuel cell humidification are the key factors for gross stack performance and overall efficiency. However, the statistical method could not reveal the distribution parameters inside PEMFC . Qin et al.…”
Section: Introductionmentioning
confidence: 99%